Хейтинг як форма девіантної комунікації в соціальних мережах - Єльнікова, Н. І.; Yelnikova, N. I. (Актуальні питання гуманітарних наук. - 2023. - Вип. 69, т. 1. - С. 176-182, 2023)
Досліджено хейтинг як форму девіантної комунікації в соціальних мережах. Проведено аналіз аспектів дискурсивної зумовленості та засобів виявлення девіантної мовленнєвої поведінки хейтерів, які залишають свої коментарі під публікаціями українських медіаперсон. Зауважено, що серед дискурсоутворювальних чинників, що визначають виникнення хейтингу як різновиду девіантної інтернет-комунікації, виокремлюють такі особливості мережевої взаємодії, як анонімність, дистанційованість, вільне самовираження, ускладненість особистісної ідентифікації коментатора, опосередкованість і верифікація потенційно можливих протиправних дій. Виявлено особливості інтернет-комунікації хейтерів на лексико-семантичному та морфологічному рівнях. З’ясовано, що для вираження своєї точки зору, а також для вербальної оцінки отриманої інформації хейтери застосовують лексику, у якій закладена зневажлива конотація, і використовують дисфемізацію стилістично нейтрального значення лексеми для надання негативної оцінки висловлюванню.

As you know, the communicative function of Internet communion today becomes а paramount thing not only for the majority of users, but also for specialists in various fields of knowledge, particularly in philology. The article examines hating as a form of deviant communication in social networks. An analysis of aspects of discursive conditioning and means of detecting a deviant speech behavior of haters who leave their comments under the publications of Ukrainian media persons was carried out. It is noted that among the discourse-forming factors that determine the emergence of hating as a type of deviant Internet communication, such features of a network interaction as anonymity, distancing, free expression, complexity of personal identification of a commentator, indirectness and verification of potentially illegal actions stand out. The material of the study was the messages ha been left by haters on the social network «Instagram» on the pages of the Ukrainian media persons. The peculiarities of online communication of haters at the lexical-semantic and morphological levels were studied. It was found out that to express their point of view, as well as to verbally assess the received information, haters use vocabulary with a derogatory connotation, and also use dysphemization of the stylistically neutral meaning of the lexeme to give a negative assessment to the statement.

Исследован хейтинг как форма девиантной коммуникации в социальных сетях. Проведен анализ аспектов дискурсивной обусловленности и средств выявления девиантного речевого поведения хейтеров, оставляющих свои комментарии под публикациями украинских медиаперсон. Замечено, что среди дискурсообразующих факторов, определяющих возникновение хейтинга как разновидности девиантной интернет-коммуникации, выделяют такие особенности сетевого взаимодействия, как анонимность, дистанцированность, свободное самовыражение, усложненность личностной идентификации комментатора, опосредованность и верификация потенциально возможных противоправных действий. Выявлены особенности интернет-коммуникации хейтеров на лексико-семантическом и морфологическом уровнях. Выяснено, что для выражения своей точки зрения, а также для вербальной оценки полученной информации хейтеры применяют лексику, в которой заложена пренебрежительная коннотация, и используют дисфемизацию стилистически нейтрального значение лексемы для придания отрицательной оценки выражению.
Hating as a form of deviant communication in social networks
Keywords: хейтинг; девіантна комунікація; хейтер; медіапростір; соціальні мережі; лексико-семантичний рівень; морфологічний рівень; hating; deviant communication; hater; media space; social networks; lexical-semantic level; morphological level; девиантная коммуникация; хейтеры; медиапространство; социальные сети; лексико-семантический уровень; морфологический уровень